2016
DOI: 10.1113/jp273137
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of noradrenergic enhancement on transcranial direct current stimulation‐induced neuroplasticity in humans

Abstract: Noradrenaline affects cognition and motor learning processes via its impact on long-term potentiation (LTP) and depression (LTD). We aimed to explore the impact of single dose and chronic administration of the selective noradrenaline reuptake inhibitor (NRI) reboxetine (RBX) on plasticity induced by transcranial direct current stimulation (tDCS) in healthy humans via a double-blinded, placebo-controlled, randomized crossover study. Sixteen healthy volunteers received placebo or single dose RBX (8 mg) before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 53 publications
(129 reference statements)
3
32
0
Order By: Relevance
“…Seven studies provided data on a‐tDCS in their placebo arms (Nitsche et al ., , , ; Grundey et al ., ; Batsikadze et al ., ; Lugon et al ., ; Kuo et al ., ). Pooled data from these studies showed a significant effect on CSE (SMD 0.31, 95% CI 0.19 to 0.42, P < 0.00001) and non‐significant heterogeneity ( I 2 = 2%, P = 0.42) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies provided data on a‐tDCS in their placebo arms (Nitsche et al ., , , ; Grundey et al ., ; Batsikadze et al ., ; Lugon et al ., ; Kuo et al ., ). Pooled data from these studies showed a significant effect on CSE (SMD 0.31, 95% CI 0.19 to 0.42, P < 0.00001) and non‐significant heterogeneity ( I 2 = 2%, P = 0.42) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, the establishment of the long-lasting after-effects depends on membrane potential changes as well as modulations of N-methyl-D-aspartate (NMDA) receptor efficacy, which can induce long-term potentiation and long-term depression like effects. [85][86][87] However, more mechanistic and in vivo studies need to be performed to better understand how tDCS can influence cortical activity and act on neuroplasticity.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
“…Stronger stimulation, more stimulation sessions, and tDCS in less severely affected patients might generate larger effects, as implied by the results of the study by Brunoni, Valiengo, et al (2013). Moreover this study is in favor of a superior efficacy of combined tDCS and pharmacological intervention, which makes sense, given the deficient LTP hypothesis of depression, the positive impact of both agents alone on symptoms, and the strengthening of tDCS-induced LTP-like plasticity by application of serotonin or noradrenaline reuptake-inhibitors (Kuo et al, 2016;Nitsche, Boggio, et al, 2009). tDCS seems to be relatively well tolerated; however, hypomania, and manifest mania were described in relatively rare cases, which might hint to the importance of 'dosed' stimulation.…”
Section: Depressionmentioning
confidence: 74%
“…Future studies should be designed to identify optimally suited stimulation protocols with regard to the abovementioned parameters, and, given the positive results of the studies by Brunoni, Valiengo, et al (2013) and Valiengo et al (2013), it would make sense to conduct large multi-centre double-blinded sham-controlled trials. Apart from this, it might, furthermore, make sense to explore the potential of tDCS by elucidating the interaction of tDCS with antidepressant medication or medication known to improve the efficacy of anodal tDCS, such as D-cycloserine and reboxetine (Kuo et al, 2016;Nitsche, Jaussi, et al, 2004), combining tDCS with cognitive training of prefrontal functions, comparing the efficacy of different electrode positions directly, testing the impact of remote 'boosting' sessions of tDCS on the maintenance of therapeutic effects, broadening the application of tDCS to specific depression syndromes, such as post-stroke depression, and exploring the cognitive effect of tDCS in more detail. The results of these studies might help to identify optimized stimulation protocols, to learn more about the cognitive impact of tDCS in depression, and suitable patient groups.…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation